Prevalence and management of severe asthma in the Nordic countries: findings from the NORDSTAR cohort. Issue 2 (3rd April 2023) - Hansen, Susanne; von Bülow, Anna; Sandin, Patrik; Ernstsson, Olivia; Janson, Christer; Lehtimäki, Lauri; Kankaanranta, Hannu; Ulrik, Charlotte; Aarli, Bernt Bøgvald; Fues Wahl, Hanna; Geale, Kirk; Tang, Sheila Tuyet; et al.
Background: Real-life evidence on prevalence and management of severe asthma is limited. Nationwide population registries across the Nordic countries provide unique opportunities to describe prevalence and management patterns of severe asthma at population level. In nationwide register data from Sweden, Norway and Finland, we examined the prevalence of severe asthma and the proportion of severe asthma patients being managed in specialist care. Methods: This is a cross-sectional study based on the Nordic Dataset for Asthma Research (NORDSTAR) research collaboration platform. We identified patients with severe asthma in adults (aged ≥18 years) and in children (aged 6–17 years) in 2018 according to the European Respiratory Society/American Thoracic Society definition. Patients managed in specialist care were those with an asthma-related specialist outpatient contact (only available in Sweden and Finland). Results: Overall, we identified 598 242 patients with current asthma in Sweden, Norway and Finland in 2018. Among those, the prevalence of severe asthma was 3.5%, 5.4% and 5.2% in adults and 0.4%, 1.0%, and 0.3% in children in Sweden, Norway and Finland, respectively. In Sweden and Finland, 37% and 40% of adult patients with severe asthma and two or more exacerbations, respectively, were managed in specialist care; in children the numbers were 56% and 41%, respectively. Conclusion: In three Nordic countries, population-based nationwide data demonstrated similar prevalence of severe asthma. In children, severe asthma was a rare condition. Notably, a large proportion of patients with severe asthma were not managed by a respiratory specialist, suggesting the need for increased recognition of severe asthma in primary care. In nationwide cohorts of all asthma patients from three Nordic countries, the prevalence of severe asthma was comparable: 3.5–5.4% in adults and 0.3–1% in children. Many patients with severe asthma are not managed in specialist care. https://bit.ly/3vM1kMg